The Success Factors of Knitting Small Medium Enterprises: A Case Study on SME Centre - Chumaidiyah, Endang; Kamil, Anton Abdulbasah; Amani, Husni (ExcelingTech, 2020)
SMEs are the largest business group that plays an important role in driving the economy because it involves large numbers of workers. But SMEs have lower productivity compared to large scale businesses. Therefore, The SMEs are needed to improve the competitiveness by identifying critical success factors. This paper aims to identify critical success factors in knitting SMEs by using factor analysis methods. The results obtained show that of the 10 variables identified in the group into 4 factors, namely the main factor (25.6%), supporting factors (20.8%), local competitor factors (12.3%), and global competitor factors (11.7 %). The four factors in accordance with their priorities are the factors that determine the success of an SME or critical success factors with an influence level of 70.4%. The main factors impacted the success of SMEs from internal organizations are marketing, machine, and creativity in product design. Then from the external environment is government policies.